Association between pregnant women's experience of stress and partners' fly-in-fly-out work - Dawson C. Cooke; Garth Kendall; Jianghong Li; Michael Dockery (Women and Birth, 2019)
[Background:] It is relatively common in Western Australia for men to commute long distances and work away from home for extended periods of time, often referred to as fly-in-fly-out work. Women are particularly susceptible to the effects of stress during pregnancy, and the absence of a partner due to working away could be an additional risk to their wellbeing. While there is little published fly-in-fly-out literature, there is evidence that working non-standard hours, more generally, has a negative impact on health and well-being of workers and their families. [Aim:] To determine if there is an association between pregnant women's report of stress and their partners working fly-in-fly-out, and if so, is there is a differential impact that is dependent on family socioeconomic status. [Methods:] Data from a Western Australian pregnancy cohort study were analysed (n=394 families). Couples completed self-report ratings of anxiety, depression, stress, family functioning, and stressful life events. Comparisons were made between three groups: fly-in-fly-out workers, non-fly-in-fly-out regular schedule workers, and non-fly-in-fly-out irregular schedule workers. [Results:] After controlling for a range of variables, women's stress was significantly associated (p<.05) with their partners working fly-in-fly-out. Neither women's education, partners' occupation nor an interaction between partners' fly-in-fly-out work and partners' occupation were significantly associated with women's stress. [Conclusion:] There is some evidence that the pregnant partners of fly-in-fly-out workers perceive their lives to be more stressful than women whose partner works non-fly-in-fly-out regular schedules.
Keywords: 330; FIFO; Long distance commute; Pregnancy; Work; Stress